Electrical and mechanical properties of ferroelectric lead zirconate titanate/tungsten oxide ceramics - Jiansirisomboon S. (2014)
Ferroelectric PZT/xWO3 ceramics (when x = 0, 0.5, 1, 3 and 5 vol%) were fabricated from PZT and nano-sized WO3 powders by a solid-state mixed-oxide method. Phase characterization suggested that the reaction between PZT and WO3 occurred during the sintering. This reaction seemed more pronounced with increasing the content of WO3. The maximum density at approximately 97% of the theoretical value was achieved at 1 vol% of WO3 addition. The grain size was reduced with an addition of WO3 particles from ∼7.8 μm for PZT to ∼1.8 μm for 0.5 vol% WO3 and ∼0.8 μm for 1-5 vol% WO3. Mechanical properties of PZT could be improved with an addition of WO3 nano-particulates. The addition of 0.5 vol% WO3 could maintain good electrical properties while increasing WO3 significantly reduced dielectric and piezoelectric constants of the PZT. © 2007 Elsevier Ltd and Techna Group S.r.l.